Green Growth Diagnostics: Regional Aspect - BELIK, Irina; STARODUBETS, Natalia; YACHMENEVA, Alena; ALIKBEROVA, Tamila (Journal of Environmental Management and Tourism; Vol 10 No 2 (2019): JEMT VOlume X Issue 2(34) Spring 2019DO - 10.14505//jemt.v10.2(34).23, 2019)
Green or a low-carbon economy is recognized by the world community as the main way to achieve sustainable development. Russia, among other countries, also sets the relevant goals, which are connected with the necessity to correlate the consequences of growing population pressure and the planet's natural resources depletion. The article demonstrates the feasibility of use of additional diagnostic tools to study green economy and to track the dynamics of the structural changes taking place at the regional level through the transformation of the local economy towards low-carbon development. For this purpose, it is proposed to introduce indicators, which will characterize the sustainable use of resources, the climatic and environmental components of green development, the level of economic growth, the Human Development Index and the number of jobs created in green sectors. The article shows the results of the diagnostic testing of the green growth changes in the region based on the proposed number of indicators. The diagnostic was performed in one of the key industrial regions of Russia -- Sverdlovsk Oblast. The resulting picture presents a retrospective analysis of green economic development for the period between 2007 and 2015, uncovers the problems, which may hinder implementation of this model, and identifies the ways for their solution.